Toxicants target cell junctions in the testis: Insights from the indazole-carboxylic acid model - Cheng, C Yan (Spermatogenesis, 2015)
There are numerous types of junctions in the seminiferous epithelium which are integrated with, and critically dependent on the Sertoli cell cytoskeleton. These include the basal tight junctions between Sertoli cells that form the main component of the blood–testis barrier, the basal ectoplasmic specializations (basal ES) and basal tubulobulbar complexes (basal TBC) between Sertoli cells; as well as apical ES and apical TBC between Sertoli cells and the developing spermatids that orchestrate spermiogenesis and spermiation. These junctions, namely TJ, ES, and TBC interact with actin microfilament-based cytoskeleton, which together with the desmosomal junctions that interact with the intermediate filament-based cytoskeleton plus the highly polarized microtubule-based cytoskeleton are working in concert to move spermatocytes and spermatids between the basal and luminal aspect of the seminiferous epithelium. In short, these various junctions are structurally complexed with the actin- and microtubule-based cytoskeleton or intermediate filaments of the Sertoli cell. Studies have shown toxicants (e.g., cadmium, bisphenol A (BPA), perfluorooctanesulfonate (PFOS), phthalates, and glycerol), and some male contraceptives under development (e.g., adjudin, gamendazole), exert their effects, at least in part, by targeting cell junctions in the testis. The disruption of Sertoli–Sertoli cell and Sertoli–germ cell junctions, results in the loss of germ cells from the seminiferous epithelium. Adjudin, a potential male contraceptive under investigation in our laboratory, produces loss of spermatids from the seminiferous tubules through disruption of the Sertoli cell spermatid junctions and disruption of the Sertoli cell cytoskeleton. The molecular and structural changes associated with adjudin administration are described, to provide an example of the profile of changes caused by disturbance of Sertoli-germ cell and also Sertoli cell-cell junctions.